(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2020)
The scope of our article is to address the intertwining of the judiciary and capitalism, through an analysis of the social forms and ideology that characterize this mode of production. Unlike traditional views, we seek to demonstrate, based on authors who take a critical perspective, the peculiarity of the judiciary in the context of capitalist society, whose specificity does not allow us to establish points of contact with the judicial functions present in pre-capitalist historical times. We will also address the originality of the legal-procedural form of our time, as a result of the secondary derivation between the legal form and the state political form, both of which, in turn, are directly derived from the commodity form. We will also deal, albeit briefly, with the clashes surrounding the issue of judicial activism in Brazil. The theoretical basis of our study lies primarily in the Marxist reading of society and the legal phenomenon.